Genomes 3 - Brown, T A (Garland Science Publishers, 2007)
Covering molecular genetics from the basics through to genome expression and molecular phylogenetics, this book is the latest edition of this pioneering textbook. Newly updated to incorporate the recent major advances, this book is an invaluable companion for any undergraduate throughout their studies in molecular genetics. This book builds on the achievements of the previous two editions by putting genomes, rather than genes, at the centre of molecular genetics teaching. Recognising that molecular biology research was being driven more by genome sequencing and functional analysis than by research into genes, this approach has gathered momentum in recent years.